La popularización del saber y la « generación de las modernas » : revistas y espacios femeninos en la España de entreguerras - Matilde Eiroa (Amnis)
The article proposes the analysis of two scopes of spreading knowledge in the inter-war period: on the one hand the places of sociability of the so called « modern women generation », such as the Lyceum Club or the « Residencia de Señoritas »; on the other hand two key magazines in the process of formation of this generation: Mundo Femenino, and Cultura integral y femenina. The examination of both public spaces allows discovering the role of cultural institutions and the gender association in women instruction. It allows, as well, verifying to what extent the women magazines contributed to the popularization of culture and scientific knowledge between the thriving women of those times. It proposes, to a certain extent, that both surroundings worked like agents of social changes that happened with the proclamation of II the Spanish Republic in April of 1931.